Deoxy Derivatives of L-like 5'-Noraristeromycin - Hinton, Shante (2012)
Several base variations of 2'- and 3'-deoxy derivatives of (+)-4'-deoxy-5'-noraristeromycin have been prepared from enantiomerically pure precursors following standard purine nucleoside construction. These carbocyclic nucleosides were evaluated against hepatitis B virus (HBV) and found to be inactive. No cytotoxicity to the cell line was observed.